Camera Roll, Action! Non-specialist Undergraduate English Learners’ Perceptions of Using Video Production in Learning English - Mahardika, I Gusti Ngurah Agung Wijaya; Widiati, Utami; Bhastomi, Yazid; Suryati, Nunung (Journal of University Teaching and Learning Practice, 2021)
This paper reports on non-specialist undergraduate English learners' perceptions about the use of video project in learning English, which was adopted to counter students’ low English learning motivation. Data were collected from the first-semester students of Hinduism Education Department in a state university in Indonesia. The students were taught English using group-based video projects where they developed their own scenarios, shot, edited, and presented their videos by themselves. Video production was used to enable the learners to use English actively and improve learners’ motivation to learn English in the future by promoting the learner’s sense of achievement. Using a questionnaire and interview, the researcher obtained data on students’ perceptions of the use of video project in learning English. The study results showed that the learners have a positive perception of the impact of video production on their English learning (dimension mean of 4.07). The learners also reported that video production improved their confidence in their English and increased their motivation (dimension mean of 4.17). Lastly, the learners considered video production as a feasible, enjoyable, and affordable way to learn English (dimension mean of 4.29).